SPECTROSCOPIC NON-ADIABATIC DIAGRAMS FOR MULTIMODAL PULSATING STARS - Daszynska, J.; Cugier, H. (Одеські астрономічні публікації, 2017)
Recently we proposed a new method of mode identification based on spectroscopic nonadiabatic diagrams (Cugier & Daszynska 2001, As.Ap., 377, 113). Our results are for β Cephei models. These diagram involve the amplitude ratios and phase differences calculated from various oscillating parameters measured from line profiles. We found that the spectroscopic observables are especially useful to determine m values. In this paper we investigate the case of multimodal pulsating models.